Contemporary multicenter outcomes of continent cutaneous ileocecocystoplasty in the adult population over a 10‐year period: A Neurogenic Bladder Research Group study. Issue 6 (7th June 2020) - Cheng, Philip J.; Keihani, Sorena; Roth, Joshua D.; Pariser, Joseph J.; Elliott, Sean P.; Bose, Sanchita; Khavari, Rose; Crescenze, Iryna; Stoffel, John T.; Velaer, Kyla N.; Elliott, Christopher S.; Raffee, Samantha M.; et al.
Abstract: Aims: Evidence is sparse on the long‐term outcomes of continent cutaneous ileocecocystoplasty (CCIC). We hypothesized that obesity, laparoscopic/robotic approach, and concomitant surgeries would affect morbidity after CCIC and aimed to evaluate the outcomes of CCIC in adults in a multicenter contemporary study. Methods: We retrospectively reviewed the charts of adult patients from sites in the Neurogenic Bladder Research Group undergoing CCIC (2007‐2017) who had at least 6 months of follow‐up. We evaluated patient demographics, surgical details, 90‐day complications, and follow‐up surgeries. the Mann‐Whitney U test was used to compare continuous variables and χ ² and Fisher's Exact tests were used to compare categorical variables. Results: We included 114 patients with a median age of 41 years. The median postoperative length of stay was 8 days. At 3 months postoperatively, major complications occurred in 18 (15.8%), and 24 patients (21.1%) were readmitted. During a median follow‐up of 40 months, 48 patients (42.1%) underwent 80 additional related surgeries. Twenty‐three patients (20.2%) underwent at least one channel revision, most often due to obstruction (15, 13.2%) or incontinence (4, 3.5%). Of the channel revisions, 10 (8.8%) were major and 14 (12.3%) were minor. Eleven patients (9.6%) abandoned the catheterizable channel during the follow‐up period. Obesity and laparoscopic/robotic surgical approach did not affect outcomes, though concomitant surgery was associated with a higher rate of follow‐up surgeries. Conclusions: In this contemporary multicenter series evaluating CCIC, we found that the short‐term major complication rate was low, but many patients require follow‐up surgeries, mostly related to the catheterizable channel.